Large-scale construction project management : understanding legal and contract requirements - Tan, Yan (Boca Raton, FL : CRC Press, 2020)
"A majority of large-scale construction and major infrastructure projects are funded by public funds from taxpayers. However, these projects are often subject to severe delays and cost overruns. This book introduces integrated approaches to project management and control mechanisms to effectively manage large-scale construction projects. It explains integrated project governance with regard to time, cost, risk, change, contract management, and more. Further, it discusses the legal issues of scheduling delays and disruptions with regard to the Delay and Disruption Protocol (Society of Construction Law) as well as Forensic Schedule Analysis guidance (American Association of Cost Engineering)"--
Introduction -- Construction Contracts -- Project Planning -- Commercial Management -- Risk Management -- Change Management -- Project Reporting -- Alternative Dispute Resolutions -- Integrated Project Control -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Construction contracts; Construction industry -- Law and legislation; Construction industry -- Management; Project management; Construction industry -- Risk management; TECHNOLOGY / Construction / General; TECHNOLOGY / Engineering / Civil